Steroids in the assessment of prenatal development. Issue 612 (October 1976) - Chamberlain, G.; Kitchin, Y.
Abstract : Methods for identifying the fetus at risk and monitoring fetal well-being as pregnancy progresses are now an established part of prenatal care in the Western World. In this short review the use of steroids in the assessment of prenatal development is discussed. The metabolism of oestrogens, progestogens, corticosteroids and androgens during pregnancy is outlined and the relative merits, in terms of usefulness and practicability, of urinary and plasma steroid assays are discussed.